Community flood resilience assessment in Jamuna floodplain: A case study in Jamalpur District Bangladesh. (1st April 2022) - Haque, Md Munjurul; Islam, Sabina; Sikder, Md Bahuddin; Islam, Md Saiful
Abstract: Flooding is a recurrent event in Bangladesh, and it causes loss to life and properties. In flood risk management, the assessment of community resilience is standard practice. This study aims to assess the community flood resilience of some selected Upazilas of Jamalpur District in Bangladesh. Appropriate indicators were selected to determine flood resilience through an extensive literature review. The indicators were provided with a weight based on the expert's judgment. A structured questionnaire, consisting of appropriate questions, was prepared to collect data for all indicators. A total of 400 households were surveyed from five flood-affected Upazilas, including Dewanganj, Islampur, Madarganj, Melandaha, and Sharishabari to collect primary data. Resilience index is an analytical tool representing a numeric score ranging from 0 to 1 for each variable. The value obtained from the field survey had been divided by the weighted value of that particular variable to calculate the variable resilience index (VRI). Then, by averaging the VRI values, composite resilience index (CRI) values were calculated. The calculated CRI values are 0.30, 0.37, 0.36, 0.36, and 0.38 out of 1 in Dewanganj, Islampur, Madarganj, Melandaha, and Sharishabari Upazila, respectively, which suggest low community resilience to flooding. This study recommends enhancing the social, economic, institutional, and physical components, which can be executed through community awareness and disaster preparedness programs, to help communities strengthen resilience and cope with floods.